2020
DOI: 10.1088/1402-4896/abb5c6
|View full text |Cite
|
Sign up to set email alerts
|

Dark solitons and modulational instability of the nonlinear left-handed transmission electrical line with fractional derivative order

Abstract: This paper unearths solitary wave in a simplified electrical model practical of the nonlinear left-handed transmission electrical line having series capacitance and shunt inductance. The detailed study of the practical model digs out that by taken a good parameter of the lattice, the obtained equation from the evolution of the wave envelope can be reduced to a one-dimensional fractional nonlinear Schrödinger equation, which gives the pipe of the dark solitons propagation. By simulating transient circuits, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Therefore, we aim to investigate the parameters influencing the frequency of the wave. For related studies, see [37][38][39]. We begin by assuming that equation (1) is subjected to a small perturbation.…”
Section: Modulation Instabilitymentioning
confidence: 99%
“…Therefore, we aim to investigate the parameters influencing the frequency of the wave. For related studies, see [37][38][39]. We begin by assuming that equation (1) is subjected to a small perturbation.…”
Section: Modulation Instabilitymentioning
confidence: 99%
“…In 2017, Zhang et al [36] demonstrated theoretically and numerically that the Lévy index affects the fastest growing frequency and MI bandwidth and gain. Correspondingly, dark soliton [37] and bright soliton [38], instability modulations in the FSE have also been studied.…”
Section: Introductionmentioning
confidence: 99%
“…[20,21] Furthermore, considering that the all-fiber laser has the advantages of high reliability, easy operation and maintenance, and good compatibility, [22][23][24] it could be anticipated that the domain-wall soliton trains in the allfiber structure laser could greatly enhance applications in optical sensing, optical communication, and soliton multiplexed systems. [25,26] In this paper, we report the experimental observation of DW dark solitons in a ring laser with an all-fiber structure. To be more compact and compatible, the laser is mode-locked by a segment of thulium-doped fiber.…”
Section: Introductionmentioning
confidence: 99%